Malaria Is Associated With Kaposi Sarcoma-Associated Herpesvirus Seroconversion in a Cohort of Western Kenyan Children. (29th November 2020) - Sabourin, Katherine R; Daud, Ibrahim; Ogolla, Sidney; Labo, Nazzarena; Miley, Wendell; Lamb, Molly; Newton, Robert; Whitby, Denise; Rochford, Rosemary
Abstract: Background: We aimed to determine whether Plasmodium falciparum infection affects age of Kaposi sarcoma-associated herpesvirus (KSHV) seroconversion in Kenyan children. Methods: Kenyan children (n = 144) enrolled at age 1 month, from 2 sites with different levels of malaria transmission (stable/high vs unstable/low) were followed to age 24 months. Plasma was tested for KSHV antibodies using enzyme-linked immunosorbent assay (ELISA; K8.1 and LANA) and a multiplex bead-based assay (K8.1, K10.5, ORF38, ORF50, and LANA) and whole blood tested for P. falciparum DNA using quantitative PCR. Cox proportional hazards models were used to assess associations between P. falciparum DNA detection, malaria annualized rate ( P. falciparum detections/person-years), and enrollment site (malaria-high vs malaria-low) with time to KSHV seroconversion. Results: KSHV seroprevalence was 63% by age 2 years when assessed by multiplex assay. Children with P. falciparum were at increased hazards of earlier KSHV seroconversion and, among children with malaria, the hazard of becoming KSHV seropositive increased significantly with increasing malaria annualized rate. Children from the malaria-high transmission region had no significant difference in hazards of KSHV seroconversion at 12 months but were more likely to become KSHV seropositive by age 24 months. Discussion: Malaria exposure increases the risk for KSHV seroconversion early in life. Abstract : In Kenyan children followed to 24 months of age, children with a prior malaria infection became KSHV seropositive at a faster rate than children without malaria. Our findings will direct future work on KSHV infection prevention in sub-Saharan Africa.